2018
DOI: 10.3390/jmse6020058
|View full text |Cite
|
Sign up to set email alerts
|

Using Coupled Hydrodynamic Biogeochemical Models to Predict the Effects of Tidal Turbine Arrays on Phytoplankton Dynamics

Abstract: The effects of large scale tidal energy device (TED) arrays on phytoplankton processes owing to the changes in hydrodynamic flows are unknown. Coupled two-dimensional biogeochemical and hydrodynamic models offer the opportunity to predict potential effects of large scale TED arrays on the local and regional phytoplankton dynamics in coastal and inshore environments. Using MIKE 21 Software by DHI (https://www.dhigroup.com), coupled two-dimensional biogeochemical and hydrodynamic models were developed with simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Laboratory flume studies help understand wake recovery and turbulence due to tidal energy extraction (e.g., [71,72]), which can support the understanding of potential effects. Until large arrays are deployed and field measurements are collected, numerical models provide the greatest insight into the potential effects of MRE deployment on oceanographic systems, although relatively few modeling studies address environmental effects directly (e.g., [73][74][75]). However, model validation is needed through additional field data collection.…”
Section: Changes In Oceanographic Systems Associated With Mrementioning
confidence: 99%
“…Laboratory flume studies help understand wake recovery and turbulence due to tidal energy extraction (e.g., [71,72]), which can support the understanding of potential effects. Until large arrays are deployed and field measurements are collected, numerical models provide the greatest insight into the potential effects of MRE deployment on oceanographic systems, although relatively few modeling studies address environmental effects directly (e.g., [73][74][75]). However, model validation is needed through additional field data collection.…”
Section: Changes In Oceanographic Systems Associated With Mrementioning
confidence: 99%
“…In order to analyze the tide characteristics of Tianjin port, current data is monitored during the test period. We obtain the flow speed and flow direction during the test period by smoothing the current data which have been eliminated the large error and filtered [45][46][47][48]. Fig.…”
Section: Current Analysismentioning
confidence: 99%
“…Having its cut-in speed at only 1.2 m/s, it is capable of functioning in slower currents, while operating at depths between 60 and 120 m [14]. The potential impacts of the Deep Green on local marine ecosystems have already been studied [15,16], where it was found that phytoplankton dynamics and benthic communities were unlikely to be altered by its operation. A preliminary LCA was also done on Deep Green at an early planning stage [17].…”
Section: Introductionmentioning
confidence: 99%